PENGARUH SISTEM PEREKRUTAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN DIRUMAH SAKIT - Atika Wulandari (Journal of Hospital Administration and Management (JHAM), 2021)
Recruitment is the first step for hospitals in finding human resources that match the hospital's needs. Recruitment of human resources is in line with employee performance, if recruitment is carried out correctly, the hospital will produce human resources who have good performance as well. Methods: methode carried out are observation and documentation. Results: The Result obtained based on the journals discussed are that there are better result in improving employee performance.